2019
DOI: 10.2478/cjf-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Plastic Waste and Microplastics in the Seas and Oceans: Impact on Marine Organisms

Abstract: A global problem of today is the large amount of waste in the seas and oceans, primarily plastic waste. It is estimated that every year 1.25 to 2.41 million tons of plastic material is being carried by rivers into the seas and oceans. Waste is a major problem for marine organisms, causing entanglement, choking, strangulation, malnutrition and death. In 1972 the problems caused by microplastics, particles smaller than 5 mm, were first observed. Such particles bind pathogenic microorganisms on to their surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Some authors have reported that an estimated five trillion plastics are floating particles on the ocean surface (Eriksen et al 2014 ; PlasticsEurope 2016 , 2017 ). The increased incidence of plastics in various compartments of the aquatic environment has been associated with human population density, highlighting a direct relationship between human population increase and plastic pollution (Engler 2012 ; Kurtela and Antolović 2019 ). Reports on the origin of microparticles (MPs) indicate that large plastic debris disintegrate and become smaller (< 1 mm) MPs via photolytic, mechanical, and biological degradation processes in the environment (Browne et al 2007 ; Andrady 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported that an estimated five trillion plastics are floating particles on the ocean surface (Eriksen et al 2014 ; PlasticsEurope 2016 , 2017 ). The increased incidence of plastics in various compartments of the aquatic environment has been associated with human population density, highlighting a direct relationship between human population increase and plastic pollution (Engler 2012 ; Kurtela and Antolović 2019 ). Reports on the origin of microparticles (MPs) indicate that large plastic debris disintegrate and become smaller (< 1 mm) MPs via photolytic, mechanical, and biological degradation processes in the environment (Browne et al 2007 ; Andrady 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, 80% of plastic waste originate from littering on land (Andrady 2011 ), making plastics and its degradation products major components of freshwater pollution (Williams and Simmons 1996 ; Balas et al 2001 ; Eerkes-Medrano et al 2015 ) and as vectors for the transfer of other contaminants into the aquatic environment (Koelmans et al 2016 ). Concerns related to the incidence of these emerging pollutants in the aquatic environment have been largely attributed to their persistence, ubiquity, and toxic potential (Endo et al 2005 ; Engler 2012 ; Kurtela and Antolović 2019 ). Further, once ingested, MPs may transfer through the habitat, feeding mode, and trophic level (Batel et al 2016 ; Mattsson et al 2015 , 2017 ; Tosetto et al 2017 ; Au et al 2017 ; Windsor et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Being the largest and growing consumer of plastics, the packaging industry represents the primary supplier of waste plastics from the environment [ 1 , 2 , 3 ]. All this mismanaged plastic waste is becoming a source of soil and groundwater pollution that eventually enters our food chain as microplastics [ 4 ]. Once inside the human body, the microplastics can cause toxicity, oxidative stress, cytokine secretion, cell damage, and inflammatory and immune reactions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This forecast has become disturbing due to serious environmental pollution problems. Nowadays, millions of tons of plastic wastes (including plastic bottles, plastic bags, or food wrappers) accumulate in landfills and pollute coastlines and oceans [4,5]. The reason is the short service life of these products, which in some cases is less than a week, and their great durability.…”
Section: Introductionmentioning
confidence: 99%